2021
DOI: 10.1017/jfm.2021.1057
|View full text |Cite
|
Sign up to set email alerts
|

The logarithmic variance of streamwise velocity and conundrum in wall turbulence

Abstract: The logarithmic dependence of streamwise turbulence intensity has been observed repeatedly in recent experimental and direct numerical simulation data. However, its spectral counterpart, a well-developed $k^{-1}$ spectrum ( $k$ is the spatial wavenumber in a wall-parallel direction), has not been convincingly observed from the same data. In the present study, we revisit the spectrum-based attached eddy model of Perry and co-workers, who proposed the emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 56 publications
10
16
0
Order By: Relevance
“…The first overlap region yields a k −1 variation, and the second a k −5/3 variation, where k is the streamwise wavenumber. These results are in line with 'classical' expectations, but high Reynolds number experiments at Princeton failed to confirm such trends (Morrison et al 2002(Morrison et al , 2004Rosenberg et al 2013;Vallikivi, Ganapathisubramani & Smits 2015a), as did the most recent measurements in the Melbourne tunnel (Hwang, Hutchins & Marusic 2021). It appears that the existence of a well-developed k −1 spectrum is not a necessary condition for the presence of a logarithmic wall-normal dependence of the turbulence intensity.…”
Section: Nanoscale Thermal Anemometry Probesupporting
confidence: 83%
See 3 more Smart Citations
“…The first overlap region yields a k −1 variation, and the second a k −5/3 variation, where k is the streamwise wavenumber. These results are in line with 'classical' expectations, but high Reynolds number experiments at Princeton failed to confirm such trends (Morrison et al 2002(Morrison et al , 2004Rosenberg et al 2013;Vallikivi, Ganapathisubramani & Smits 2015a), as did the most recent measurements in the Melbourne tunnel (Hwang, Hutchins & Marusic 2021). It appears that the existence of a well-developed k −1 spectrum is not a necessary condition for the presence of a logarithmic wall-normal dependence of the turbulence intensity.…”
Section: Nanoscale Thermal Anemometry Probesupporting
confidence: 83%
“…2002, 2004; Rosenberg et al. 2013; Vallikivi, Ganapathisubramani & Smits 2015 a ), as did the most recent measurements in the Melbourne tunnel (Hwang, Hutchins & Marusic 2021). It appears that the existence of a well-developed spectrum is not a necessary condition for the presence of a logarithmic wall-normal dependence of the turbulence intensity.…”
Section: Turbulent Stress Measurementsmentioning
confidence: 77%
See 2 more Smart Citations
“…Since our Superpipe data has , a power law is not expected to appear clearly. Moreover, Hwang, Hutchins & Marusic (2022) showed that even without the presence of a power law, the framework of the spectral AEM can still successfully yield a log law for , which is a key feature of wall-bounded turbulence. Therefore, within the context of the spectral AEM, the existence of a power law may not be a necessary feature of wall-bounded turbulence.…”
Section: Resultsmentioning
confidence: 99%